Effect of Fimasartan versus Valsartan and Olmesartan on Office and Ambulatory Blood Pressure in Korean Patients with Mild-to-Moderate Essential Hypertension: A Randomized, Double-Blind, Active Control, Three-Parallel Group, Forced Titration, Multicenter, Phase IV Study (Fimasartan Achieving Systolic Blood Pressure Target (FAST) Study) - Chung WB; Ihm SH; Jang SW; Her SH; Park CS; Lee JM; Chang K; Jeon DS; Yoo KD; Seung KB (Dove Medical Press, 2020)
Woo-Baek Chung,1 Sang-Hyun Ihm,2 Sung-Won Jang,3 Sung-Ho Her,4 Chul Soo Park,5 Jong-Min Lee,6 Kiyuk Chang,1 Doo-Soo Jeon,7 Ki-Dong Yoo,8 Ki-Bae Seung1 1Division of Cardiology, Department of Internal Medicine, Seoul St. Mary’s Hospital, The Catholic University of Korea, Seoul, Republic of Korea; 2Division of Cardiology, Department of Internal Medicine, Bucheon St. Mary’s Hospital, The Catholic University of Korea, Seoul, Republic of Korea; 3Division of Cardiology, Department of Internal Medicine, St. Paul’s Hospital; 4Daejeon St. Mary’s Hospital, The Catholic University of Korea, Seoul, Republic of Korea; 5Division of Cardiology, Department of Internal Medicine, Yeouido St. Mary’s Hospital, The Catholic University of Korea, Seoul, Republic of Korea; 6Division of Cardiology, Department of Internal Medicine, Uijeongbu St. Mary’s Hospital, The Catholic University of Korea, Seoul, Republic of Korea; 7Division of Cardiology, Department of Internal Medicine, In-Cheon St. Mary’s Hospital, The Catholic University of Korea, Seoul, Republic of Korea; 8Division of Cardiology, Department of Internal Medicine, St. Vincent’s Hospital, The Catholic University of Korea, Seoul, Republic of KoreaCorrespondence: Sang-Hyun IhmDivision of Cardiology, Department of Internal Medicine, Bucheon St. Mary’s Hospital, College of Medicine, The Catholic University of Korea, 14647, 327, Sosa-ro, Bucheon-si, Gyeonggi-do, Republic of KoreaTel +82-32-340-7027Fax +82-32-340-2669Email heartihmsh@yahoo.co.krKi-Bae SeungDivision of Cardiology, Department of Internal Medicine, Seoul St. Mary’s Hospital, College of Medicine, The Catholic University of Korea, 06591, 222, Banpo-daero, Seocho-gu, Seoul, Republic of KoreaTel +82-2-2258-1134Fax +82-2-591-1506Email kbseung@catholic.ac.krPurpose: Head-to-head comparison of the blood pressure (BP) lowering effect of fimasartan versus valsartan, with olmesartan as a reference, on office blood pressure and ambulatory BP.Patients and Methods: Of the 369 randomly assigned patients in this study, 365 hypertensive patients were referred as the full analysis set and divided into 3 groups with a 3:3:1 ratio (fimasartan group: 155, valsartan group: 157, olmesartan group: 53). After the 2-week single-blind placebo run-in period, initial standard doses of 60-mg fimasartan, 80-mg valsartan, and 10-mg olmesartan were administered for 2 weeks, then forcibly up-titrated higher doses (fimasartan 120 mg, valsartan 160 mg, olmesartan 20 mg) were given for 4 weeks. ABP was measured before and after the 6-week treatment. Primary endpoint was reduction of sitting office systolic BP (SiSBP) of fimasartan compared to valsartan after 6 weeks. Secondary endpoints were reduction of sitting office diastolic BP (SiDBP) and 24 hrs, day-time, and night-time mean systolic and diastolic ABP (ASBP, ADBP) after 6 weeks.Results: Patients’ mean age was 58.34± 7.68 years, and 289 patients were male (79.18%). After the 6-week treatment, SiSBP reduction of fimasartan and valsartan were − 16.26± 15.07 and − 12.81± 13.87 (p=0.0298) and SiDBP were − 7.63± 9.67 and − 5.14± 8.52 (p=0.0211). Reductions in 24 hrs mean ASBP were − 15.22± 13.33 and − 9.45± 12.37 (p=0.0009), and ADBPs were − 8.74± 7.55 and − 5.98± 7.85 (p=0.0140). Reductions of night-time ASBPs were − 16.80± 15.81 and − 10.32± 14.88 (p=0.0012), and those of night-time ADBPs were − 8.89± 9.93 and − 5.55± 9.70 (p=0.0152). Reduction of BP in olmesartan group did not demonstrate significant difference with fimasartan group in all end-points.Conclusion: Fimasartan 120-mg treatment demonstrated superior efficacy in reduction of SiSBP, SiDBP, and 24 hrs ASBP and ADBP compared to valsartan 160 mg. Reduction of night-time ASBP from baseline was largest in fimasartan group, suggesting that fimasartan may be effective for recovering dipping pattern.NCT number: NCT02495324 (Fimasartan Achieving SBP Target (FAST) study).Keywords: 24 hr ambulatory blood pressure monitoring, angiotensin receptor blocker, essential hypertension, antihypertensive